Laboratory evaluation of the efficacy of bucket chlorination guidelines at inactivating Vibrio cholerae for waters of varying quality. (30th June 2022) - String, Gabrielle M.; Huang, Annie; Lantagne, Daniele
Abstract: Bucket chlorination, where chlorine is dosed directly into water collection containers, is a point-of-source water treatment intervention commonly implemented in cholera outbreaks. There is little previous data on chlorine efficacy against Vibrio cholerae in different waters and appropriate dosage regimes. We evaluated V. cholerae reduction and free chlorine residual (FCR) in waters with four turbidities (1/5/10/50 NTU), two total organic carbon (TOC) concentrations (0.4, 1 mg/L), and two dosing schemes (fixed-dose of 2 or 4 mg/L, variable-dose based on jar testing) treated with three chlorine types (HTH, NaOCl, NaDCC). We found that chlorine was efficacious at reducing V. cholerae by ≥2.75 to ≥3.63 log reduction value (LRV); variably dosed reactors were dosed higher, met ≥0.5 mg/L FCR at 30 min, and had higher LRVs ( p =0.024) than fixed doses; and low TOC reactors had more samples ≥0.2 mg/L FRC at 4 h ( p =0.007). Our results are conservative, as internationally recommended additives to create test water increased chlorine demand, highlighting the challenge of replicating field conditions in laboratory testing. Overall, we found that chlorine can efficaciously reduce V. cholerae ; we recommend further research on appropriate chlorine demand for test waters; and we recommend establishing appropriate chlorine doses based on source water and taste/odor acceptability in bucket chlorination programs. HIGHLIGHTS: Bucket chlorination is a point-of-collection emergency water treatment program. We tested the efficacy of chlorine dosing guidelines against Vibrio cholerae in waters of varying turbidity and total organic carbon. Chlorine efficaciously reduces V. cholerae and is recommended at appropriate doses in bucket chlorination programs. Chlorine decayed rapidly – test water chlorine demand may be higher than natural waters. Graphical Abstract